SINTESIS METIL ASETILSALISILAT DAN METIL BENZOILSALISILAT DARI MINYAK GANDAPURA (WINTERGREEN OIL) DAN UJI AKTIVITAS SEBAGAI ANALGESIK - , BOWO APRIYANTO, Prof. Sabirin Matsjeh, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aspirin is an analgesic and a derivative of salicylic acid. The synthesis of methyl acetylsalicylate and methyl benzoylsalicylate as aspirin analog has been carried out by esterification. Methyl acetylsalicylate and methyl benzoylsalicylate were synthesized by reacting methyl salicylate from wintergreen oil with acetyl chloride and benzoyl chloride in pyridine (modified Schotten-Baumann method). The analgesic activity of the synthesized compound was evaluated by acetic acid induction method (writhing test) in male mice strain swiss. The orally doses methyl acetylsalicylate and methyl benzoylsalicylate are 50, 100 and 200 mg/kgBW. Acetylsalicylic acid at dose of 100 mg/kgBB as a positive control and carboxylmethylcellulose 0.5% as a negative control. The synthetic products is methyl acetylsalicylate (mp. 51 Â°C) with yielded of 59.07% and methyl benzoylsalicylate (mp. 87 Â°C) with yielded of 48.44%. Both products had a white solid and odour like aspirin. Structure elucidation those synthetic products by infrared spectrofotometer (FTIR), 1H-NMR and mass spectrofotometer showed the structure of methyl acetylsalicylate and methyl benzoylsalicylate. Respectively, the analgesic percent protection of methyl acetylsalicylicate was 20.92%, 47.70% and 63.39%. Respectively, the analgesic percent protection of methyl benzoilsalicylate was 34.31%, 69.04% and 83.47%. Methyl acetylsalicylate and methyl benzoylsalicylate had a stronger analgesic activity than aspirin (32.01%) at the same dose (100 mg/kgBW). It can be concluded that methyl acetylsalicylate and methyl benzoylsalicylate have an analgesics activity.